ANALYSIS OF RELIGIOUS VALUES IN THE BOOK “STORIES IN THE QURAN: MEANS OF OPTIMIZING RELIGIOUS AND MORAL DEVELOPMENT OF CHILDREN - Ahmad Rifai; Husin; Helda; Abdul Rashid bin Abdul Aziz (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
One way for parents to guide their children is to read fairy tales. When reading stories, parents can also insert messages that aim to stimulate the religious and moral development of children. The purpose of this research is to analyze the religious values ​​contained in the book Tales in the Al-Quran, Published by Pelangi Mizan as a tool that can be used by parents or educators to optimize children's religious and moral development.This research method is library research. The results of the research show that there are religious values ​​contained in the bookStories in the Quran, Published by Pelangi Mizan. The religious value in this study refers to Muhaimin's perspective which includes 3 aspects, namely: human relationship with God, human relationship with humans and human relationship with nature. The religious values ​​contained in the book Acts in the Quran Published by Pelangi Mizan, namely 1) the relationship between humans and God is an attitude of piety, gratitude, praising God and surrender. 2) the relationship between humans and humans, namely not insulting other people and being arrogant 3) the relationship between humans and nature, namely loving animals, which is contained in the story of Prophet Sulaiman.